Multisystemic diseases and ethnicity: a focus on lupus erythematosus, systemic sclerosis, sarcoidosis and Behçet disease - Petit, A.; Dadzie, O.E. (British journal of dermatology (1951), 2013)
Summary We present an overview of the association between ethnicity and the clinical and epidemiological aspects of four multisystemic diseases: lupus erythematosus, systemic sclerosis, sarcoidosis and Behçet disease. In particular, we highlight observed ethnic differences in cutaneous manifestations of these diseases. This article should help guide clinical management, as well as serve to highlight future areas for research. What's already known about the subject? A multisystemic disease is a disorder in which several organs or systems are affected by the same pathological process. Clinical experience supports an association between ethnicity and the clinical and epidemiological aspects of some multisystemic diseases. What does this study add? This study presents an evidence‐based review of the impact of ethnicity on epidemiological and cutaneous features of four multisystemic diseases: lupus erythematosus, systemic sclerosis, sarcoidosis and Behçet disease.